Corporal Punishment in Light of the Criminal Policies of the Religious State - Mohammad Mahdi AnjomShoae (حقوق بشر, 2011)
In the Islamic Republic of Iran in which a Muslim jurist has absolute authority over all its pillars and affairs, the supreme leader’s views play an important role both directly in determining the criminal policy for confronting and preventing behavioral and moral corruptions (as a part of general policies of system), and indirectly in passing and approving laws in accordance and agreement with the standards of Islamic Shariah. Disciplining and punishing children as a part of criminal policy in the jurisprudential teachings of Islam are recognized as a right for parents and the approved laws also confirm this. However, restrictions such as observing the limits of custom and expediency are the requirements for exercising this right that has a great influence on adjusting it and protecting children. Disciplining child offenders by the courts and juvenile centers is one of the mechanisms that govern the criminal policy to confront the abnormal behavior of children and in fact replace corporal punishment and rough behavior which result in normal controlled reactions. In the international view, adoption of CRC (Convention on the Rights of Child) by the Islamic Republic of Iran with reservations can raise some misconceptions regarding the contradiction between domestic law and religious opinions on the matter with international law and may cast doubt on its international commitments. In addition to describing the legal status of corporal punishment of children, this study will reveal the position of the legal system of the Islamic Republic of Iran towards this important international document more than before. در نظام جمهوری اسلامی ایران که ولایت مطلقۀ فقیه بر تمام ارکان و شوؤن آن حاکم است، نظرات مقام رهبری به صورت مستقیم در تعیین سیاست جنایی برای مقابله و پیشگیری از انحرافات اخلاقی و رفتاری (به عنوان بخشی از سیاستهای کلی نظام) و به صورت غیرمستقیم در تصویب قوانین موافق و منطبق بر موازین شرعی ایفای نقش میکند. تأدیب و تنبیه کودکان به عنوان جزیی از سیاست جنایی، در آموزههای فقهی اسلام، به عنوان حقی برای اولیاء به رسمیت شناخته شده و قوانین مصوب نیز بر آن صحه گذاشته است؛ در عین حال، محدودیتهایی همچون رعایت حد متعارف و مصلحت ، شرط اعمال این حق دانسته شده که تأثیر به سزایی در تعدیل آن و حمایت از کودکان دارد. تأدیب کودکان بزهکار از طریق دادگاههای اطفال و کانونهای اصلاح و تربیت، از جمله تمهیداتی است که به نظاممند کردن سیاست جنایی مقابله با رفتارهای نابهنجار کودکان و در واقع جایگزینی تنبیه بدنی و رفتارهای خشن با عکسالعملهای رسمی کنترل شده منجر میگردد. از منظر فرامرزی، الحاق مشروط جمهوری اسلامی ایران به کنوانسیون حقوق کودک میتواند شبهۀ مغایرت قوانین داخلی و نظرات فقهی ناظر به موضوع، با مقررات بینالمللی را ایجاد نموده و تعهدات جهانی کشور را زیر سؤال ببرد. مطالعۀ این موضوع، علاوه بر توضیح جایگاه قانونی و شرعی تنبیه بدنی کودکان، موضع نظام حقوقی جمهوری اسلامی ایران را در قبال این سند مهم بینالمللی بیش از پیش آشکار مینماید.